Proccessing cerate-zirconate nanopowder at supercritical conditions via batch-wise reactor system / Nafisah Osman and Mohd Azlan Mohd Ishak - Osman, Nafisah; Mohd Ishak, Mohd Azlan (Research Management Institute (RMI), 2016)
Protonic conductors of ceramic perovskite-type oxides (ABO3) have captured attention of researchers worldwide for technological purpose in fuel cells, batteries, steam electrolyser, etc. The best candidate amongst them is the perovskite-type oxides of Ba(Ce,Zr)03 which is known to exhibit high mechanical and chemical stability along with good conductivity. This proton conductor is the best applicant as electrolyte for solid oxide fuel cells (SOFC) in the presence of hydrogen and/or water vapour at intermediate temperatures (400-750 °C) There are very limited information available regarding the durability of cells based on the cerate-zirconate, for example, Y-doped Ba(Ce,Zr)03 electrolyte. Indeed, synthesizing cerate-zirconate electrolyte especially supercritical fluid method is a critical challenge as previous report has found that only 2-3 metal element can be obtained a single perovskite phase. However, to the best of our knowledge this route has not yet been carried out to synthesize ceramics compounds with four metal elements In the presence work, high-pressure-high-temperature (HP-HT) batch-wise reactor system was used to synthesise BaCeo.54Zro.36Y01O2.95 (BCZY) perovskite powder using different parameter such as reaction pressure, reaction temperature and solvent as SCF media. Considering the advantages of Wet Chemical Method (WCMs) and SCF properties, an approach towards the combination of both synthesis routes was used in this work. BCZY was synthesise by sol-gel assisted supercritical fluid method using different heating proceses. The phase formation was studied to investigate the formation of any secondary using X-ray diffractometer (XRD).